1999
DOI: 10.1097/00001756-199904260-00002
|View full text |Cite
|
Sign up to set email alerts
|

Attention changes the peak latency of the visual gamma-band oscillation of the EEG

Abstract: To investigate the physiological role of visual gamma-band oscillation (GBO), we calculated the event-related dynamics of the EEG power-spectrum for paired visual stimuli (S1 and S2) with or without attention in 12 subjects. The visual stimuli elicited transient increases in the GBO power (around 40 Hz), which were maximal over the parietal area. The peak GBO increase appeared around 300 ms after stimulus onset, but its latency was shorter after S1 and longer after S2 under the 'with attention' than under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
1
14
0
9
Order By: Relevance
“…The ERS values obtained using the original method agree with the results obtained in previous works: ERS ≈ 10–20% [54,55]. More recent studies [56] observed an increase in gamma-band activity in different tasks (emotional stimuli, face recognition, and motor control) using invasive techniques, such as electrocorticography.…”
Section: Discussionsupporting
confidence: 88%
“…The ERS values obtained using the original method agree with the results obtained in previous works: ERS ≈ 10–20% [54,55]. More recent studies [56] observed an increase in gamma-band activity in different tasks (emotional stimuli, face recognition, and motor control) using invasive techniques, such as electrocorticography.…”
Section: Discussionsupporting
confidence: 88%
“…For example, cats (Gray et al, 1989; Lakatos et al, 2004), rats (Sukov and Barth, 2001) and mice (Ehrlichman et al, 2009; Lazarewicz et al, 2010; Nase et al, 2003) show a peak in phase-locked gamma activity (∼40 Hz) within the first 100 ms of auditory or visual stimulation, following a time course similar to that observed in humans (Pantev et al, 1991; Shibata et al, 1999). Indeed, similar evoked GBRs have been observed in insects during sensory stimulation, suggesting that gamma synchrony is a phylogenetically conserved neural coding mechanism (MacLeod and Laurent, 1996).…”
Section: 0 Gamma Oscillations In Preclinical Studies Of Schizophreniamentioning
confidence: 76%
“…Advances in neuroimaging technologies such as the hemodynamic functional imaging methodologies (fMRI and PET) and the ability to conduct high-density multi-channel electro- and magneto- encephalographic recordings (EEG and MEG) have allowed for unprecedented advances in our understanding of the physiology of human selective attention. This report specifically addresses evidence for the role of oscillatory brain mechanisms in selective attention (e.g., Vanni et al, 1997; Foxe et al, 1998; Gruber et al, 1999; Shibata et al, 1999; Sokolov et al, 1999; Worden et al, 2000; Sauseng et al, 2005; Yamagishi et al, 2005; Kelly et al, 2006; Thut et al, 2006; Rihs et al, 2007; Snyder and Foxe, 2010). …”
mentioning
confidence: 86%